Answer:
none
Step-by-step explanation:
to solve this equation we would say that
let
x + y = 5 .............................. equation 1
x + y = 6 .................................... equation 2
from equation 2
x + y = 6 .................................... equation 2
x = 6 -y...................................... equation 3
substitute for x into equation 1
x + y = 5 .............................. equation 1
6 - y + y = 5
from here this equation cannot be solved further therefore it has no solution.
Answer:
C
Step-by-step explanation:
In a Pythagorean triple the square on the longest side is equal to the sum of the squares on the other 2 sides.
A
longest side = 10 ⇒ 10² = 100
6² + 8² = 36 + 64 = 100
A is a Pythagorean triple
B
longest side = 17 ⇒ 17² = 289
8² + 15² = 64 + 225 = 289
B is a Pythagorean triple
C
longest side = 9 ⇒ 9² = 81
5² + 8² = 25 + 64 = 89
89 ≠ 81
C is not a Pythagorean triple
D
longest side = 13 ⇒ 13² = 169
5² + 12² = 25 + 144 = 169
D is a Pythagorean triple
Answer:
G=7
Step-by-step explanation:
4(g-1)=24
4g-4=24
4g=28
g=7
I'm pretty sure it's 22%
If it's not, then I'm sorry!!
Answer:
16
Step-by-step explanation:
Simply plug in 2 for a, then 6 for b and substitute
(2+6)2
Then do order of operations to simplify PEMDAS
First what's inside the parenthesis
(8)2
Then multiply
16.